Aster yomenaextract ameliorates pro‐inflammatory immune response by suppressing NF‐κB activation in RAW 264.7 cells. Issue 2 (February 2018) - Hwang, Kyung‐A; Hwang, Yu‐Jin; Song, Jin
Abstract : Background: : Aster yomena, an edible vegetable, is a perennial herb found in Korea, China, Japan, and Siberia. It is used as folk medicine to treat cough, bronchial asthma, and insect bites. A . yomena was recently shown to have antioxidant and anti‐asthmatic activities. Studies have not yet evaluated the anti‐inflammatory effects of the various solvent fractions of A . yomena . We investigated the anti‐inflammatory activity of various solvent fractions (hexane, dichloromethane, ethyl acetate, and butanol) from ethanol extract of A . yomena in activated macrophages. Methods: : Anti‐inflammatory effects of A . yomena were investigated to determine the inhibitory effects of A . yomena against inflammation using RAW 264.7 mouse macrophages. To measure the effects of A . yomena on inflammatory mediators and cytokines, we used the following methods: cell viability assay, flow cytometry assay, ELISA assay, real‐time PCR and western blotting. Results: : The dichloromethane fraction exhibited marked anti‐inflammatory activities by inhibiting nitric oxide (NO) and prostaglandin E2 production and mRNA expression of inducible isoforms of NO synthase, cyclooxygenase‐2, and cytokines (tumor necrosis factor α, interleukin (IL)‐6, IL‐1β) in response to lipopolysaccharide (LPS) stimulation. Moreover, dichloromethane fraction from A . yomena significantly inhibited the transactivation of nuclear factor (NF)‐κB and the nuclear translocation of the NF‐κB p50 and p65 subunits. Conclusion: : These results suggest that A . yomena may have anti‐inflammatory activity in vitro, suggesting this herb could be a source of natural anti‐inflammatory agents.